2006
DOI: 10.1111/j.1600-6143.2006.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Diabetes Mellitus in Moderate Term Survivors of Liver Transplantation

Abstract: The prevalence and risk factors for diabetes mellitus after liver transplantation are not well understood. Thus, we sought to identify independent risk factors for the development of diabetes after liver transplantation using currently accepted medical criteria.We studied the prevalence and risk factors in 253 adult recipients transplanted at UCLA between January 1998 and December 2002. Analysis of the retrospective data was performed using demographic, immunosuppression and liver disease variables. Factors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 43 publications
4
28
0
Order By: Relevance
“…Factors that are usually associated with diabetes in the general population such as increased BMI, lipid abnormalities or fasting glucose were not found to be independently related to PTDM in our study population. These fi ndings are comparable with results obtained in another study [22] . Factors that might contribute to the increased incidence of PTDM in men include diff erences in life style and in immunosupression response compared to females [23,24] .…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Factors that are usually associated with diabetes in the general population such as increased BMI, lipid abnormalities or fasting glucose were not found to be independently related to PTDM in our study population. These fi ndings are comparable with results obtained in another study [22] . Factors that might contribute to the increased incidence of PTDM in men include diff erences in life style and in immunosupression response compared to females [23,24] .…”
Section: Discussionsupporting
confidence: 95%
“…In our study women were less aff ected by this sequel than men in univariate analysis. Previous studies already demonstrated that male sex is a risk factor for development insulin resistance and PTDM after kidney and liver transplantation [21,22] . Factors that are usually associated with diabetes in the general population such as increased BMI, lipid abnormalities or fasting glucose were not found to be independently related to PTDM in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…In a series from Harvard [42] , which compared 47 HCV-positive to 111 HCV-negative cases, HCV infection was an independent risk factor for the development of T2D after LT (hazard ratio 2.5, P = 0.001). These data were repeatedly confirmed by later studies [43][44][45][46][47][48][49] , with one exception from the [University of California, Los Angeles (UCLA)] series, in which the lack of association may have been a consequence of the excess representation of HCVpositive patients [50] . Several predisposing factors were identified across the studies: impaired fasting glucose and a maximum lifetime BMI over 25 kg/m 2 [49] , age and male gender [48] , serum HCV RNA level after LT [51] , and use of tacrolimus [45] or steroid boluses [43] .…”
Section: Association Between Hcv and T2dsupporting
confidence: 63%
“…More understanding of the role of diabetes in transplantation and of its proper management should contribute to achieving improvement in long-term survival. Identification of modifiable risk factors for the development of NODM, such as body mass index or immunosuppression should be one of the strategies for the management of NODM (17,18).…”
Section: Discussionmentioning
confidence: 99%